User friendly Natural Dyes For Printed Textiles - Ong, W.F. (Universiti Malaysia Sarawak, (UNIMAS), 2011)
In recent years, natural dyes have been gaining popularity in the textile and craft industries as it believed to be ecologically friendly. Various researches have been carried out to explore the natural dyes for textile dyeing but not for textile printing.